La discusión filosófica de la contestación de fray José Jimeno, del Colegio de Crucíferos de Querétaro, al manifiesto del señor Hidalgo (2021)
What was experienced in Querétaro during Independence goes beyond the legend of the conspiracy and its discovery. The division between those who were in favor of the insurgent movement and those who were against it marked Querétaro society, although the realistic position predominated. Friar José Jimeno, reader and guardian of the Apostolic College of the Holy Cross for two periods, was in favor of the counterinsurgent cause. However, the historical preference for Hidalgo has made us lose sight of the value of the philosophical‑theological arguments of the Franciscan friar against the proclamations of the father of the country. What is proposed, very modestly, in this work is an approach to the Reply of Friar José Jimeno, of the College of Crucifers of Querétaro, to Mr. Hidalgo’s Manifesto as an event that occurred in the city of Querétaro during the insurgent process of Independence of Mexico, since the studies on counterinsurgent propaganda, in its discursive form, neglect the argumentative, philosophical-theological peculiarity of friar José Jimeno's reply and frame it in a homogeneous set of insults against Hidalgo and the independence movement. In the end, it is noted that the Franciscan friar's criticism of Hidalgo is similar to what was expressed by Derrida regarding the North American Declaration of Independence.